Bilateral deficit: origins, mechanisms, and implications for strength training. http://dx.doi.org/10.5007/1980-0037.2012v14n6p749 - Cíntia Ehlers Botton; Ronei Silveira Pinto (Universidade Federal de Santa Catarina, 2012)
Several studies have demonstrated a lower capacity to generate force when the exercises of the training program are performed bilaterally than when compared to the sum of the strength produced by each limb separately. This phenomenon, one that has been well documented in the scientific literature, is called "bilateral deficit." The underlying mechanisms of the bilateral deficit are not fully clear, but they seem to be related to neural mechanisms, such as a blockage of the brain hemispheres, that may occur during bilateral contractions thus reducing the activation of motor units and therefore the strength produced. In relation to each execution form (unilateral and bilateral) in the long term, the adaptations appear to be specific to the type of contraction performed in the training. Therefore, due to the relevance of the exercises performed unilaterally and bilaterally in the strength training program, as well as the long-term effect of each execution form in the morphological and neurological adaptations to training, the aim of this article is to characterize the bilateral deficit phenomenon, to explore its main causative mechanisms, and to discuss the influence of each training type (unilateral and bilateral) in the adaptations of strength training.